SISTEM RESI GUDANG SEBAGAI ALTERNATIP SUMBER PEMBIAYAAN UNTUK KOMODITAS PERTANIAN - Anggo Doyoharjo (Universitas Slamet Riyadi, 2008)
ABSTRACT: The price of farming commodity is always low during the harvest season Iit is resulted in the income of the farmers. The issue of warehouse financing will postpone the selling. In fact, warehouse financing can be purchased and even can be used as a credit guarantee. Using this warehouse financing, farmers will have access in getting loans from banks with warehouse finance guarantee. If the credit is paid, the guarantee can be returned and the owner has the right to regret the goods. In the other hand, if the owner cant pay the bill, the goods is cold in auction or through direct by the bank to pay the owner’s credit. KEYWORDS: Warehouse system financing.